Disentangling the taxonomical uncertainties about the presence of Cistus pouzolzii Delile in the Iberian Peninsula - Sanchez-Gómez, Pedro; Cánovas, José Luis; Lahora, Agustín; Catalán, Antonio E.; Jiménez-Martínez, Juan Francisco (Mediterranean Botany, 2024)
Cistus pouzolzii is a species distributed in the western Mediterranean. Its populations are located in France and North Africa, being absent in the Iberian Peninsula.. It was described by Delile, but its taxonomic and nomenclatural status has been discussed by several authors, mainly based on its particular combination of morphological characters. We have recently found several populations of a Cistus species whose morphological characters match those of C. pouzolzii. To confirm the taxonomic identity of these populations, a comparative study was performed using herbarium specimens of C. pouzolzii from France and North Africa. In addition, two chloroplast regions were sequenced to study the phylogenetic relationships between the newly discovered Iberian populations and the rest of the species of the genus Cistus, including the sequences belonging to C. pouzolzii from France and Morocco previously used. Both analyses (morphological and phylogenetic studies) confirmed that the specimens sampled in the Iberian populations were C. pouzolzii. Furthermore, both the nomenclature of this species and its conservation status are briefly discussed.